Antioxidant activities of agarwood hydrosol - Hashim, Yumi Zuhanis Has-Yun; Ab. Rahman, Erra Fazira; Zainurin, Nur Aimi Aliah; Mohamed Azmin, Nor Fadhillah (International Institute of Halal Research and Training (INHART), IIUM, 2018)
This present work sets to investigate agarwood hydrosols as potential source of antioxidants. The compounds present in absolute (AFAH), oil (OFAH) and water (WAFAH) fraction of agarwood hydrosols were investigated using GCMS. The antioxidant properties were then studied using three different methods: (2,2'-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid)) assay (ABTS), (2,2-diphenyl-1-picrylhydrazyl) assay (DPPH) and total phenolic assay. All three fractions were found to have antioxidant properties with OFAH having the highest antioxidant activities. At 1000 μg/ml, OFAH showed inhibition with 90.06% ± 0.06 (ABTS) and 37.61% ± 0.59 (DPPH). Total phenolic assay revealed that OFAH has high total phenolic content (31.15 μg GAE/g sample± 0.00) which may contribute to high antioxidant activities. Based on principal component analysis (PCA), cyclohexanecarboxylic acid, hexanoic acid, phenol, 2,4-bis(1,1-dimethylethyl)- were found to separate OFAH from AFAH and WAFAH. In conclusion, agarwood hydrosols showed antioxidant properties which can further developed as ingredients for halal nutraceutical and cosmeceutical products.